Review about Luis Íñigo Fernández: Brief History of Spain I. The roots. Brief History of Spain II. The way of modernity - Equipo Editorial (ADIDE Federación, 2011)
TÍTULO: BREVE HISTORIA DE ESPAÑA, I. LAS RAÍCES. EDITORIAL: NOWTILUS ISBN: 9788497639187 TÍTULO: BREVE HISTORIA DE ESPAÑA, II. EL CAMINO DE LA MODERNIDAD. EDITORIAL: NOWTILUS ISBN: 9788497639217